The role of stereotactic radiosurgery(SRS) in treatment of cerebral metastases from lung cancer. - Gazal (2022)
Introduction Brain metastases are very common in lung cancer patients. In non-small cell lung cancer (NSCLC) almost 40% of patients will develop brain metastases during their illness and this number may be even higher in patients with mutation of the epidermal growth factor receptor (EGFR). Stereotactic radiosurgery (SRS) has become a well-established first-line therapy for patients with a limited number of brain metastases. The aim of this analysis was therefore to evaluate the efficacy of SRS in lung cancer brain metastases with different histopathological features and to assess the pattern and imaging features of brain metastases. Patents and methods We retrospectively reviewed the case records of patients with lung cancer and evidence of brain metastases from the database of IPO Porto between 2011 and 2020. The data obtained were statistically analyzed. Results We analyzed 84 patients with brain metastasis from lung cancer. We found that during follow up of brain metastasis after SRS, at 3, 6 and 12 months, most of the lesions reduced or maintained their size. Patients with lesions that showed a heterogeneous contrast enhancement tended to have a higher number of lesions, diameter of lesions and levels of gross tumor volume in comparison with patients with lesions that showed homogeneous contrast enhancement. We also noted that, men tended to be older than women, both at the time of primary tumor and brain metastasis diagnosis. Smokers had higher levels of gross tumor volume than non-smokers. There was a correlation between existence of extracranial metastasis at the time of SRS and lesions with smaller diameter. Patients with symptom improvement after SRS had received higher levels of total radiation dose during SRS. Results also showed that there was a significant association between the dominant mutation of the brain tumor and the follow-up at 3, 6 and 12 months and the occurrence of new brain lesions. Conclusions SRS has proved to be an effective and appropriate choice for the treatment of patients with limited number of brain metastases of lung cancer, providing a good local control of brain metastasis. The histopathology of the brain metastasis and some imaging features of the brain metastasis from lung cancer can predict the evolution of brain metastasis after SRS, helping to define which patients are the best candidates for SRS. However, it was not possible to make a prediction about the prognosis of the brain metastasis treated with SRS based on pattern of distribution. These data support further research concerning treatment of brain metastasis from lung cancer with SRS.